Amal Assurance Bhd: Direct Marketing Dilemma a Case Study - Abd Jalil, Mohd Jafni (1999)
Over the years, life insurance industry has experienced positive growth. In 1997 when the economic downturn hit our country, the performance of the industry has reduced drastically. Still, they manage to have a positive growth but much lesser than the previous years. This dropped performance is mainly due to the lost in in vestment in the stock exchange. Although it considered as on paper loss but it gives a great impact to the ind ustry. Thanks to the people awareness on the importance of life insurance, new premium incomes have a steady growth and this actually helps the industry to maintain its position. The effect seems to be effected only on the investment part. Nevertheless the organizations in the industry are starting to find new ways to develop their business. Research and development are their main focus in order to search for new alternatives to capture larger sales. They are now focusing to meet the customer needs rather than providing services to the customers. One of the potential strategies that were seen is to go direct to the customers without the participation of agents or any other third party. With the advan cement of I n ternet technology and development of database banks, the organizations in the industry are focusing towards this type of channels. Same like any other organ izations in the ind ustry, AMAL Assurance Bhd . Have taken a step in venturin g into a new channel which is Direct Marketing. The decision made to ve nture i nto this channel was d ue to the factors mentioned previously. The needs of the customers. Today's customers are keener to convenience rather than the cost. Therefore , the focus will be on p roviding hassle free products and accord ing to their need s . Even thoug h the strategy taken was accord ing t o today's customer's trend , it cannot run from the possibility that the strategy chosen will fail. There will always be another element that ca n i nfluence the environment. Therefore in this case write-up and analysis will look at the Direct Marketing's activities in AMAL Assu rance Bhd., the proble m that they are facing a nd the possible solutions to the problems. The case will g ive the readers a broad view on what actually the main issue in the organization's Direct Ma rketing channel.